2019
DOI: 10.1186/s12885-019-5809-8
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the need for specialized palliative care in adult cancer patients – development and validation of a screening procedure based on proxy assessment by physicians and filter questions

Abstract: Background One challenge in caring for cancer patients with incurable disease is the adequate identification of those in need for specialized palliative care (SPC). The study’s aim was to validate an easy to use phenomenological screening tool. Methods The German tool is based on the National Comprehensive Cancer Network (NCCN) Palliative Care guidelines and contains ten items in five domains that focus e.g. on diagnosis, functional status, complications, comorbidities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 22 publications
0
36
0
1
Order By: Relevance
“…The importance of screening and identification of unmet symptoms and needs and the subsequent integration of specialist palliative care have been emphasized and may result in better patient-relevant outcomes [31]. The large percentage of severely affected advanced cancer patients with a recent advanced cancer diagnosis yielded in this study adds to the discussion of how burdened patients should be identified [32][33][34]. In a Delphi study with nearly 60 international experts, 11 criteria concerning a possible outpatient palliative care referral were found in a consensus process [34].…”
Section: Assessed For Eligibility (N=3155)mentioning
confidence: 85%
“…The importance of screening and identification of unmet symptoms and needs and the subsequent integration of specialist palliative care have been emphasized and may result in better patient-relevant outcomes [31]. The large percentage of severely affected advanced cancer patients with a recent advanced cancer diagnosis yielded in this study adds to the discussion of how burdened patients should be identified [32][33][34]. In a Delphi study with nearly 60 international experts, 11 criteria concerning a possible outpatient palliative care referral were found in a consensus process [34].…”
Section: Assessed For Eligibility (N=3155)mentioning
confidence: 85%
“…This percentage was lower than previous evaluations of the tool in the United States and Germany. 11 , 12 In the United States, the tool was developed and tested in patients hospitalized under the GI Oncology Service—also the most common tumor primary site in our survey—at a large US comprehensive cancer center (CCC). The GI Oncology Service was selected because they were perceived to have a high level of unmet PC need.…”
Section: Discussionmentioning
confidence: 99%
“…Five was chosen as the cut point on the basis of previous testing of the tool. 11 , 12 In these studies, a score of ≥ 5 was highly predictive for meeting one or more of the National Comprehensive Cancer Network’s (NCCN) criteria for specialist PC referral. 6 To determine the usefulness of the screening process, we sought to determine its yield, which we defined as the number of patients who screened positive who were not already referred to the specialist PC service.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations